2017
DOI: 10.18203/2320-1770.ijrcog20174196
|View full text |Cite
|
Sign up to set email alerts
|

Forearm bone mineral density in postmenopausal Indian women: correlation with calcium nutrition

Abstract: Background: Osteoporosis is characterized by low bone mass with micro architectural deterioration of bone tissue leading to enhanced bone fragility, thus increasing the susceptibility to fracture. This study was conducted with the objective of measuring forearm bone mineral density in postmenopausal Indian women and to establish a correlation with indices of calcium nutrition i.e. dietary calcium intake, calcium supplements, serum calcium, serum phosphorus, serum alkaline phosphatase and serum intact parathyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In a study conducted by Sharma S et al there was no significant correlation observed between BMD and serum phosphorus. 12 The present study is in accord with the above study showing no significant correlation.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In a study conducted by Sharma S et al there was no significant correlation observed between BMD and serum phosphorus. 12 The present study is in accord with the above study showing no significant correlation.…”
supporting
confidence: 92%
“…In study by Sharma S et al, BMD at the level of forearm was measured and the study by Keen RW et al BMD at the level of femoral neck and spine are measured and correlated. 12,13 In our study BMD at the level of lumbar spine and hip were measured using DEXA and authors found no significant correlation between BMD Lumbar spine and BMI and surprisingly significant correlation between BMD Hip and BMI was noted. This difference may be due to heterogenecity of BMD at different areas of body with different rates of osteoclastic activity which will be more in the early years of menopause leading to rapid bone loss at lumbar spine.…”
mentioning
confidence: 53%
See 1 more Smart Citation